In the garden of the world Italy to a young 19th century Chinese traveler - Castorina, Miriam (Studi e saggi, 2020)
In the garden of the world. Italy to a young 19th century Chinese traveler. On September 14th, 1859, at the first light of dawn, a young Chinese traveler named Guo Liancheng 郭連城 (1839-1866) landed in Civitavecchia, Italy, after a long journey of overland travel and months of navigation. Coming from a small village far from the capital, he was only 20 years old and was in the company of an Italian priest, Luigi Celestino Spelta. Guo was not the first Chinese man to visit Europe but before leaving, he decided to keep a daily journal of his experience, published soon after his return with the title of Xiyou bilüe西游筆略 (Brief Account of the Journey to the West). This book presents for the first time the story of Guo Liancheng, exploring a still little-known aspect of the history of the contacts between Italy and China. Following the pages of Guo Liancheng's journal, the author tries to shed light on its contents and features and to analyze the image of Italy described in the pages of Brief account of the Journey to the West, the earliest firsthand account on the Bel Paese ever published in China.